THE TRAJECTORY OF INDIGENEITY POLITICS AGAINST LAND DISPOSSESSION IN INDONESIA - Noer Fauzi Rachman; Hasriadi Masalam (Sriwijaya Law Review, 2017)
Under the New Order authoritarian regime, the state endorsed terra-nullification of the customary territories had been the basis for the stipulation of state forest (hutan negara).After the fall of the General Suharto led regime in 1998 generated a new phase for the struggles of the customary groups in different parts of the archipelago. This article examines the rise of indigeneity and counter-hegemonic indigenous legal maneuvering spearheaded by Aliansi Masyarakat Adat Nusantara (AMAN) against ongoing land dispossession in Indonesia since the fall of New Order authoritarian regime which includes the indigenous mobilizations (strategy, organization and tactics) in the post-authoritarian country, including the avenue of new types of legal activism when it comes to the creative destruction of global capitalism today. It focuses on two modes of policy advocacy and campaign against land dispossession: (a) the production of the Constitutional Court Ruling No. 35/PUU-X/2012, a new legal landmark that establishes the constitutional norm of the citizenship status of Indonesian indigenous peoples (masyarakat hukum adat) as rights bearing subjects, and the owners of their customary territory; and (b) the National Inquiry on Indigenous Peoples’ Rights held by the Indonesian National Human Rights Commission (Komnas HAM). The discussion describes The Colonialism of ‘State-Izing’ Customary Communities’ Territory, Contemporary Indigeneity Politics in Indonesia, Counter-Hegemonic Indigenous Legal Maneuvering, Judicial Review against The1999 Law No. 41on Forestry, National Inquiry on Indigenous Peoples’ Rights, and Connecting Counter-Hegemonic Indigenous Legal Maneuvering with the Grassroots Struggles which focuses on Mobilizing at Multiple Scales. It is concluded from this article that the efficacy of legal struggles is very much depend on the capacity to connect  with the grassroots mobilization by continuously promulgating the resurgence of indigeneity politics against the destructive impacts of corporatized state under the servitude of global capitalism, the indigenous movement constituents in Indonesia